The macroeconomic theory of exchange rate crises - Piersanti, Giovanni (Oxford : Oxford University Press, 2012)
An overview of the causes and consequences of speculative attacks on domestic currency and international financial turmoil. It provides a comprehensive treatment of the existing theories of exchange rate crises and of financial market runs.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Financial crises -- Econometric models; Foreign exchange rates -- Econometric models; International finance -- Econometric models; Macroeconomics -- Econometric models